2021
DOI: 10.1002/mnfr.202100210
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐Like Components of Peanut Stem and Leaf Extract Promote Sleep by Decreasing Neuronal Excitability

Abstract: Scope: Peanut stem and leaf (PSL), a traditional Chinese medicine, is widely used as a dietary supplement to improve sleep quality; however, the underlying mechanism is unclear. Here, the study aims to determine whether active compounds in PSL extract exert their effects by mediating neuronal excitability. Methods and Results: Aqueous PSL extract (500 mg kg −1 BW) increases the duration of total sleep (TS), slow wave sleep (SWS) and rapid eye movement sleep (REMS) in BALB/c mice after 7 and 14 continuous days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 95 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Flavonoids’ exceptional biological activities and nutritional properties sparked our interest in exploring their pharmacological effects on sleep. It has been demonstrated that flavonoid therapy could improve sleep problems by having fewer negative effects [ 15 ], which makes us wonder whether flavonoid intakes are also connected with sleep duration and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids’ exceptional biological activities and nutritional properties sparked our interest in exploring their pharmacological effects on sleep. It has been demonstrated that flavonoid therapy could improve sleep problems by having fewer negative effects [ 15 ], which makes us wonder whether flavonoid intakes are also connected with sleep duration and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional pharmacotherapy including tranquilizers and hypnotics, herbal medicines have fewer side effects. The flavonoids extracted from the stems and leaves of peanuts could reduce neuronal excitability to improve sleep quality [ 15 ]. There were few studies on the relationship between isoflavone intake and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…As an enantiomer, NRG-DM extracted from peanut stem and leaf promoted sleep by dampening neuronal excitability. In cortical neurons, the inhibitory activity of NRG-DM on Nav channels appeared to be more potent than that on Kv channels [ 51 ]. However, in the current study, due to the higher IC 50 value, our data showed that inhibition of Nav channels might contribute to (−)-NRG-DM-produced analgesic activity but the effect is secondary to that of Kv channels.…”
Section: Discussionmentioning
confidence: 99%
“…These include serine, hippuric acid, indole 3 propionic acid, butanediol and cytosine. Serine can promote awakening [14], and the concentration of serine can be reduced after intervention with Luohua Anshen Oral Liquid. Luohua Anshen Oral liquid has been clinically to treat insomnia more than 100,000 times, and more than 1,200 cases have been identi ed in scienti c research [12].…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%